The impact of after sales service characteristics on customer satisfaction: a case on a supermarket’s electrical appliances department. - Muraly, Ganesh Doraisamy (2019)
The purpose of this research is to investigate why the impact of after sale service influences the customer satisfaction on the electrical appliances. The study conducted was targeted to customers of large retail chain marketing electrical appliances. The primary purpose of this research is to investigate whether the impact of after sale service characteristic will affect the customer satisfaction. It was only targeted to customers who had purchased AEON electrical appliance for the past of 1 year. The target population for this research is around 500 customers. However, there is only 315 set of questionnaires is usable for analysis. The research conducted was based on quantitative methodology. The questionnaire was also designed electronically through the online survey software and distributed through emails and social networking websites. Through these questionnaires, researcher can discover more clearly and accurately about the relationship between 5 independent variables which are reliability, tangibility, responsiveness, assurance and empathy that serve as the factors to influence the customer satisfaction on the sales after service quality. The research analysis consists of normality test, reliability test, correlation coefficient and multiple regressions. Finding obtained indicated that responsiveness, reliability and tangibility is the most influence factor in influencing customer satisfaction. While, the other two factors i.e. assurance and empathy is also positive relationship with customer satisfaction. As a conclusion, the result in Pearson Correlation indicates that reliability and tangibility component has very strong, positive and significant relationship with customer satisfaction among respondent in Klang Valley.